2018
DOI: 10.1111/ecc.12814
|View full text |Cite
|
Sign up to set email alerts
|

Underestimated caregiver burden by cancer patients and its association with quality of life, depression and anxiety among caregivers

Abstract: This study examined how patients with cancer estimate caregiver burden (CB) and the association between their underestimation of CB and their caregivers' self-ratings of their quality of life (CQOLC-K; Korean version of the Caregiver Quality of Life Index-Cancer), depression and anxiety (Korean version of the Hospital Anxiety and Depression Scale). Participants consisted of 990 patient-caregiver dyads recruited from a nationwide cross-sectional survey conducted in South Korea. Medical baseline data were retrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
73
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 36 publications
(62 reference statements)
4
73
0
2
Order By: Relevance
“…Furthermore, when it comes to communication, family caregivers experience burden related to the communication regarding patient's medical status and related decisions, let alone the difficulty recognizing and expressing his/her own physical and psychological needs [17]. While communication within family helps reduce the anxiety and depression of patients with cancer [18], the caregiving-related burden of family members was not estimated accurately by the patients [19]. Rather, patient's underestimation of caregiver burden had negative effects on the caregiver's quality of life [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, when it comes to communication, family caregivers experience burden related to the communication regarding patient's medical status and related decisions, let alone the difficulty recognizing and expressing his/her own physical and psychological needs [17]. While communication within family helps reduce the anxiety and depression of patients with cancer [18], the caregiving-related burden of family members was not estimated accurately by the patients [19]. Rather, patient's underestimation of caregiver burden had negative effects on the caregiver's quality of life [19].…”
Section: Introductionmentioning
confidence: 99%
“…While communication within family helps reduce the anxiety and depression of patients with cancer [18], the caregiving-related burden of family members was not estimated accurately by the patients [19]. Rather, patient's underestimation of caregiver burden had negative effects on the caregiver's quality of life [19]. Even though the result is not surprising considering the connection between the feeling of appreciation and the sense of reward and gratification among caregivers [20,21], studies on the concordance of patient's and caregiver's rating have focused mainly on the patient's well-being as an outcome [22][23][24], not on the caregiver's well-being [19].…”
Section: Introductionmentioning
confidence: 99%
“…The issue of caregiver overload has already been studied from other perspectives such as from the cancer patient themselves and their family members, not only mothers. Furthermore, it has in fact been proven that they overlook or underestimate this issue, meaning that they do not focus on the caregiver overload (13) .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, there are prevalent problems in terms of care giving related to the lack of personal information and professional knowledge of caregivers about the disease [9,10]. In a study by Shin et al, conducted in south Korea among patients with different types of cancers in 2018, it was reported that cancer caregivers had 49.6%, 47.6%, and 43% of physical, emotional and financial problems, respectively [11]. Recent studies believe that such problems of caregivers are common in different societies, yet with various incidences due to the cultural aspects and overall situation of every country [8,12].…”
Section: Introductionmentioning
confidence: 99%